Qualitative Analysis of Emotional Distress in Cardiac Patients From the Perspectives of Cognitive Behavioral and Metacognitive Theories: Why Might Cognitive Behavioral Therapy Have Limited Benefit, and Might Metacognitive Therapy Be More Effective? - McPhillips, Rebecca; Salmon, Peter; Wells, Adrian; Fisher, Peter (Frontiers in Psychology, 2019)
Introduction: Cognitive behavioural therapy (CBT) alleviates emotional distress in mental health settings, but has only modest effects in cardiac patients. Metacognitive therapy (MCT) also alleviates depression and anxiety in mental health settings and is in its initial stages of evaluation for cardiac patients. Aim: Our objective is to compare how CBT and MCT models conceptualise cardiac patients’ distress, and to explore why CBT has had limited benefit for cardiac patients and whether MCT has the potential to be more efficacious. Method: Forty-nine cardiac rehabilitation patients, who screened positively for anxiety and/or depression, provided semi-structured interviews. We analysed transcripts qualitatively to explore the ‘fit’ of patients’ accounts of their distress with the main elements of cognitive behavioural and metacognitive theories. Four illustrative cases, representative of the diverse presentations in the broader sample, were analysed in detail and are presented here. Results: Conceptualising patients’ distress from the perspective of CBT involved applying many distinct categories to describe specific details of patients’ talk, particularly the diversity of their concerns and the multiple types of cognitive distortion. It also required distinction between realistic and unrealistic thoughts, which was difficult when thoughts were associated with the risk or consequences of cardiac events. From the perspective of MCT a single category – perseverative negative thinking – was sufficient to understand all this talk, regardless of whether it indicated realistic or unrealistic thoughts, and could also be applied to some talk that did not seem relevant from a CBT perspective. Discussion: Conceptualizing distress from the perspective of CBT presents multiple, diverse therapeutic targets, not all of which a time-limited therapy would be to address. Given the difficulty of identifying them as unrealistic or not, thoughts about disease, death or disability may not be amenable to classic CBT techniques such as reality testing. MCT proved more parsimonious and, because it did not distinguish between realistic and unrealistic thoughts, might prove a better fit to emotional distress in cardiac patients.